RELATION BETWEEN REGULATORY T CELLS, CA-125 LEVEL AND TUMOR MASS IN OVARIAN CANCER PATIENTS - E. R. Chernykh (SPb RAACI, 2014)
The relationship between various subpopulations of regulatory T-cells (Treg) and serum level of CA-125 and dynamics of Treg following surgery in ovarian cancer (OC) patients have been investigated. The typical for OC peripheral blood Treg changes (the enchantment of CD4+FoxP3+ и CD8+FoxP3+ T-cells and decrease of CD4+CD25+/CD4+CD25high Т-cells due to their migration to ascites) have been revealed only in patients with elevated CA-125 level and were not registered in patient's group with normal level of this antigen. CA-125 serum level was directly correlated to absolute count of CD4+CD25high Т-cells and was in reverse relation to CD8+FoxP3+ T-cells. Surgical removal of a tumor was accompanied by remarkable reduction of CA-125 level in all cases. However Treg changes were observed only in patients with optimal cytoreductive surgery and were evidenced by CD4+CD25+/CD4+CD25high Т-cell normalization, whereas the number of these cells in peripheral blood of patients with residual tumors after surgery remained decreased. At that percentage of CD4+FoxP3+ и CD8+FoxP3+ Т-cells 2 weeks after surgery was unchanged and their increased number was associated with persisted decrease of T-cell proliferation in response to anti-CD3 stimulation.